Idiopathic posterior laryngeal web on an adult patient. Issue 5 (21st May 2021) - Chrysovitsiotis, Georgios; Potamianos, Spyridon; Katsinis, Spyros; Kyrodimos, Efthymios
Abstract : Posterior laryngeal webs are uncommon pathologies that are usually acquired at some point in adult life. Prior and prolonged intubation is the leading cause for developing such lesions. In certain rare cases of posterior laryngeal webs, no identifiable cause can be associated with the development of this pathology. We present a case with such an idiopathic lesion. Surgery is the treatment of choice. Several techniques and modifications can be used, to achieve maximum airway release and, at the same time, ensure that restenosis will be avoided. Our patient recurred following initial treatment and a more complex revision surgery was necessary. Special attention should be given in differentiating these lesions from abductor vocal cord paralysis. Furthermore, careful investigation of the cause and individualisation of patient treatment are crucial.